Effect of Acetic Acid as Pre-Emergence Herbicide on Maize Germination - Hidayat Pujisiswanto; Prapto Yudono; Endang Sulistyaningsih; Bambang Hendro Sunarminto (Jurnal Penelitian Pertanian Terapan, 2015)
Profitable crop production starts with a weed control program that includes pre-emergence herbicides to deliver long-lasting, residual weed control. Pre-emergence herbicides are applied to prevent the germination of weed seeds. The study was conducted to determine the effect of acetic acid as a pre-emergence herbicide on maize germination. Pots experiment was conducted on August until September 2012. The experimental design used was Completely Randomized Design (CRD) single factor in four replicates. The application of pre-emergence acetic acid at several concentration, i.e. control (no acetic acid) 0%, 10% acetic acid and 20% acetic acid. The result showed that the pre-emergence aplication at 10% and 20% of the glacial acetic acid solution lowered pH were 5,12 and 5,43 respectively at one week after application, so that inhibited maize germination. No shoots and roots were grew. This was due to the increase of electrical conductivity (EC) or electrolyte leakage caused by the high permeability of the damaged membrane of seed. The EC of control treatment was 11Î¼S/cm g, compared to 10 and 20% treatment of acetic acid were 36 Î¼S / cm g and 55 Î¼S / cm g EC respectively. Increasing concentration of acetic acid caused the higher of protein content leaked, i.e. 7,95%, 7,32% and 7,03% respectively for without acetic acid treatment, 10% and 20% acetic acid. Acetic acid also inhibited respiration rate of maize seed, where the higher concentration of acetic acid produced the lower respiration rate, i.e. 31.63 mg/g/hour, 12.38 mg/g/hour and 2,75 mg/g/hour respectively for without acetic acid treatment, 10% and 20% acetic acid. Keywords : Acetic Acid, Maize (Zea mays L.), Germination, Pre-Emergence Herbicide